A Comparative Study of the Prevalence of Bacterial Strains in Early and Late-Onset Ventilator-Associated Pneumonia in Critically Ill Patients - Babak Alikiaii; Daryoush Moradi; Sarah Mousavi; Seyed Taghi Hashemi; Maryam Mosaddeq (Research Center for Rational Use of Drugs (RCRUD), 2018)
Background: This study aims to determine the prevalence of early (less than 4 days of hospitalization) -and late-onset (more than 4 days after hospitalization) ventilator-associated pneumonia in the intensive care units of Al-Zahra center in Isfahan. Methods: Through a prospective study, 100 patients with ventilator-associated pneumonia who were hospitalized in the intensive care units of Al-Zahra hospital during 2015 were investigated, and early and late onset pneumonia were determined. Moreover, the etiology of bacterial strains and other clinical and demographic characteristics were compared in two groups. Results: The patients, 23 and 77 suffered from late -and early-onset pneumonia, respectively. The mean score of pneumonia in the two groups (early -and late-onset pneumonia) was 7.3± 2.1 and 7.2±1.6, respectively, which showed no significant difference (P: 0.8). The most common types of bacteria that caused pneumonia were methicillin-resistant Staphylococcus aureus (MRSA) (43% of frequency) and Acinetobacter Baumannii (34% of frequency) in early -and late-onset pneumonia, respectively. However, the frequency distribution of the type of bacteria by the type of pneumonia was not significantly different (P:0.1). Conclusion: A significant percentage of pneumonia in intensive care units are of early-onset type, which can lead to patients' prolonged hospitalization in intensive care units and it may be lead to increased mortality rate among them. Therefore, it is recommended that the patients hospitalized in intensive care units should be carefully examined in terms of the occurrence of pneumonia symptoms.